Trade Union Recognition and Australia’s Neo-Liberal Voluntary Bargaining Laws - McCallum, Ron (Relations industrielles / Industrial Relations, 2002)
SummaryWhen Australia deregulated its economy in the 1980s, political pressures built up leading in the 1990s to the dismantling of Australia’s industry-wide conciliation and arbitration systems. New laws established regimes of collective bargaining at the level of the employing undertaking. This article analyzes the 1993 and 1996 federal bargaining laws and argues that they fail to protect the right of trade unions to bargain on behalf of their members. This is because the laws do not contain a statutory trade union recognition mechanism. The recognition mechanisms in the Common Law countries of the United States, Canada, Britain and New Zealand are examined, and it is argued that Australia should enact trade union recognition mechanisms that are consonant with its industrial relations history and practice.